Dynamic Analysis of a Closed Economy Using the IS-LM Model in Discrete Time - Gupta, Rabindra Kumar; Gupta, Anupam (Bhairahawa Campus Journal, 2024)
This study introduces an economic model with an exogenous tax rate to analyze changes in income and interest rates, employing the ISLM (Investment-Saving and Liquidity reference-Money Supply) framework in macroeconomics. The deterministic model, formulated as ODE system, is discretized into a discrete system using the Euler method. Equilibrium and stability analyses of the discrete system are performed analytically. Numerical simulations validate the analytical findings and visualize different dynamics. The results highlight the influence of parameter sensitivities on economic stability and activity.